Capitalismo de vigilância, neoliberalismo e subjetividade - Antunes, Luis Henrique (2023)
This dissertation aimed to analyze the relationship between surveillance capitalism and neoliberalism in the production of subjectivities. The study is based on the book The Age of Surveillance Capitalism, by Shoshana Zuboff, in which the author seeks to scrutinize the complex and multifaceted relationship between platforms and neoliberal economic interests. She also points out that the privacy of users is systematically attacked by companies, as they depend on a massive amount of digital data to be able to predict their behavior online. Finally, the research was able to consider the various consequences of the predominance of big tech in contemporary society, such as online hate speech, weakening of democratic values and psychological illnesses.